2014
DOI: 10.1007/s00405-014-3187-z
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inner ear imaging features at different time points of sudden sensorineural hearing loss with three-dimensional fluid-attenuated inversion recovery magnetic resonance imaging

Abstract: It has been reported that about half of patients with sudden sensorineural hearing loss (SSNHL) show high signals in the affected inner ear on three-dimensional, fluid-attenuated inversion recovery magnetic resonance imaging (3D-FLAIR MRI). These signals may reflect minor hemorrhage or an increased concentration of protein in the inner ear, which has passed through blood vessels with increased permeability. Our objective was to compare the positive ratio of the high signal in affected inner ears at different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In a study of 46 patients with sSNHL, 3D-FLAIR MRI obtained precontrast and at 10 minutes after intravenous gadolinium injection showed significant signal-intensity ratio differences. 8 These results may indicate that 10-minute delayed images are superior to 4-hour delayed images in conditions without definitive neuritis, such as sSNHL. In 4-hour delayed images, the contrast enhancement of most structures is washed out except for mild enhancement of the perilymphatic space.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study of 46 patients with sSNHL, 3D-FLAIR MRI obtained precontrast and at 10 minutes after intravenous gadolinium injection showed significant signal-intensity ratio differences. 8 These results may indicate that 10-minute delayed images are superior to 4-hour delayed images in conditions without definitive neuritis, such as sSNHL. In 4-hour delayed images, the contrast enhancement of most structures is washed out except for mild enhancement of the perilymphatic space.…”
Section: Discussionmentioning
confidence: 90%
“…Recent articles have reported that the signal-intensity ratio of the inner ear and other parts of the brain is useful in patients with sudden deafness, Ménière disease, and vestibular schwannoma. 4,[6][7][8] The signal-intensity ratio of the inner ear and brain stem may indicate disruption of the blood-labyrinthine barrier in patients with inner ear disease with 4-hour enhancement after gadolinium injection. 7 To our knowledge, the difference in inner ear signal intensity between 10-minute and 4-hour delayed MRI has not been evaluated in most patients with unilateral symptoms, however, including those with sSNHL.…”
mentioning
confidence: 99%
“…32,63 An increased contrast enhancement of the labyrinthine fluid on 3D-FLAIR is sometimes observed in ears with sudden deafness after an intravenous administration of a gadolinium-based contrast material. 32,64 This contrast enhancement suggests the breakdown of the blood-labyrinthine barrier. 63 Prognosis for hearing was not good in ears with a high signal on precontrast 3D-FLAIR.…”
Section: Visualization Of White Matter Tractsmentioning
confidence: 98%
“…22 In cases of suspected cochlear SSHL, different studies have proposed a tailored temporal bone MR imaging with 3D-FLAIR sequence to exclude abnormalities in the inner ear structures. [9][10][11][12][13][14][15] MR imaging of the temporal bone can be negative, and the SSHL is therefore defined as idiopathic, or the MR imaging can show abnormalities in the inner ear structures, suggesting a specific etiopathogenesis (vascular or inflammatory). 14 In both cases, because no trial has yet investigated different medical protocols guided by MR imaging findings, physicians continue with empiric therapy, so temporal bone MR imaging with a 3D-FLAIR sequence has not had any effect on the therapeutic management of cochlear SSHL in clinical practice.…”
Section: Current Diagnostic Work-up Of Sshlmentioning
confidence: 99%
“…[6][7][8] Over the past decade, MR imaging has provided new insights about SSHL etiology because of high-resolution sequences that are able to detect subtle changes in the inner ear. [9][10][11][12][13][14][15] However, for many reasons, the use of this imaging technique for SSHL is still not widespread. First, many radiologists are not yet aware of the possibilities offered by advanced MR imaging studies of the inner ear and/or of the possible MR imaging findings in SSHL.…”
mentioning
confidence: 99%